2021
DOI: 10.3389/fgene.2020.622494
|View full text |Cite
|
Sign up to set email alerts
|

Complete CSN1S2 Characterization, Novel Allele Identification and Association With Milk Fatty Acid Composition in River Buffalo

Abstract: The αs2-casein is one of the phosphoproteins secreted in all ruminants' milk, and it is the most hydrophilic of all caseins. However, this important gene (CSN1S2) has not been characterized in detail in buffaloes with only two alleles detected (reported as alleles A and B), and no association studies with milk traits have been carried out unlike what has been achieved for other species of ruminants. In this study, we sequenced the whole gene of two Mediterranean river buffalo homozygotes for the presence/absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 96 publications
1
8
0
Order By: Relevance
“…These are classified into three main subclasses that include Termi-nal Inverted Repeat (TIR) DNA transposons, such as hATs and mariners; rolling-circle transposons, such as Helitrons; and self-synthesizing DNA transposons, such as Mavericks [49]. INEs have been extensively investigated in ruminants [13,52,53], but studies are also available for camelids CSN2 [19], CSN3 [23], and the entire casein cluster [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These are classified into three main subclasses that include Termi-nal Inverted Repeat (TIR) DNA transposons, such as hATs and mariners; rolling-circle transposons, such as Helitrons; and self-synthesizing DNA transposons, such as Mavericks [49]. INEs have been extensively investigated in ruminants [13,52,53], but studies are also available for camelids CSN2 [19], CSN3 [23], and the entire casein cluster [3].…”
Section: Discussionmentioning
confidence: 99%
“…The sequenced regions included 752 bp at the 5 flanking region and 115/114 bp at the 3 flanking region and are identified in GenBank as ID numbers OQ730238 (C. bactrianus) and OQ730239 (C. dromedarius). The entire gene is approximately 15,000 bp long, with 14,735 bp in dromedary and 14,695 bp in Bactrian, consisting of 982 bp in exonic regions and about 14,000 bp in intronic regions (13,753 bp in dromedary and 13,713 bp in Bactrian). Exon 1 (48 bp) and the first 12 bp of exon 2 are noncoding.…”
Section: Csn1s2 Gene Structure In Camelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Caseins are an important group of proteins in milk that accounted for approximately 80% of milk proteins and are secreted by the mammary epithelial cells ( Cavaletto et al, 2008 ). There are four types of casein: α s1 -casein, α s2 -casein, β-casein, and κ-casein, all of which possess different structures and functionality, and both α s1 -casein and β-casein are major caseins ( Cosenza et al, 2021 ). Wang et al (2014) found that Pten downregulates dairy cow mammary epithelial cell secretion of β-casein.…”
Section: Discussionmentioning
confidence: 99%
“…Milk yield [14][15][16][17][18], total protein and caseins [19][20][21][22][23], fat content, fat percentage and fatty acid composition [18,20,[24][25][26][27][28][29][30], milking time [14], etc., are among the most studied traits and are of great interest to breeders' associations due to their direct link to cheese yield and economic profitability. Genetic variability and associations with dairy traits have been found for many genes of economic interest (CSN1S1, CSN1S2, CSN3, SCD, LPL, OXT, OXTR, etc.).…”
Section: Introductionmentioning
confidence: 99%